2006
DOI: 10.1111/j.0021-9029.2006.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Name? A Multiracial Investigation of the Role of Occupational Stereotypes in Selection Decisions

Abstract: Bertrand & Mullainathan (2002) found evidence that race-typed names can have a significant influence on the evaluation of re´sume´s. The current study expanded on their research by manipulating both the race (Asian American, Black, Hispanic, White) and quality of the re´sume´(high, low), and by considering occupational stereotypes as an explanatory mechanism. White male participants (N 5 155) read a fictitious re´sume´, evaluated the applicant, and judged his suitability for jobs. The results revealed that Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 21 publications
4
98
0
Order By: Relevance
“…The influence of the name prime was not found for politically liberal or moderate participants. These results are consistent with those from previous studies that demonstrated that race-typed names can negatively influence attitudes and behaviors towards minorities and out-groups [79,11]. Furthermore, while these data are consistent with previous research specifically demonstrating that President Obama’s middle name can influence people’s views of him, the present study found an effect using an American sample whereas the previous study only found a significant effect in an Israeli sample [15].…”
Section: Resultssupporting
confidence: 93%
“…The influence of the name prime was not found for politically liberal or moderate participants. These results are consistent with those from previous studies that demonstrated that race-typed names can negatively influence attitudes and behaviors towards minorities and out-groups [79,11]. Furthermore, while these data are consistent with previous research specifically demonstrating that President Obama’s middle name can influence people’s views of him, the present study found an effect using an American sample whereas the previous study only found a significant effect in an Israeli sample [15].…”
Section: Resultssupporting
confidence: 93%
“…32 These studies do not distinguish on the basis of race, ethnicity, culture, or background of the faculty. Studies of unconscious bias in employment suggest that in job recruitment, black and Hispanic faculty members are less likely to be considered for leadership positions, 33 particularly for high status positions, 34 but the impact on faculty advancement remains to be studied. One study of faculty promotion rates showed lower rates of promotion for all underrepresented minority faculty in U.S. medical schools, but subpopulations of men and women within these groups were not studied.…”
Section: The Trajectory Of Advancement For Women In Academic Medicinementioning
confidence: 99%
“…Relying on birth records in California, Fryer and Levitt show how substantially naming patterns differ by race: ''More than half of all Blacks have names that are at least four times as likely to be given to Blacks…there are relatively few individuals carrying names that are similarly likely for Blacks and Whites' ' (2004, p. 776). Studies also show that distinctively black-sounding names are linked to a wide variety of negative outcomes; audit studies and field experiments have found that people with black-sounding names are much less likely to be called for a job interview (Bertrand and Mullainathan 2003;King et al 2006), much less likely to receive a response in a housing audit (Friedman et al 2010), and much less likely to be responded to by state legislative offices in requests for help registering to vote (Butler and Broockman 2009). Black names have also been linked to lower test scores through teachers having diminished expectations of students with these names (Figlio 2005).…”
Section: Platform and Name As A Mediator Of Evaluations Based On Racementioning
confidence: 99%